Empowerment as A Quality Improvement Human Resources Through The Implementation of Total Quality Management - Muhammad Ikhsannudin; Poetri Leharia Pakpahan (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2021)
This paper is a research that examines the empowerment of human resources through the application of total quality management at SMK Miftahul Huda Ngroto Grobogan that this school is always experiencing development and progress according to the times so it is interested to be researched. This type of research uses a qualitative approach, and data collection techniques are through observation and interviews. The research data were presented in a descriptive narrative form. Total quality management is a scientific field that refers to quality, which will improve the quality of human resources in educational institutions, both from educators and students. So as to create superior and competitive educational output. From the results of the research, SMK Miftahul Huda Ngroto Grobogan uses a planned sustainable management system with reference to the total quality management system standard as a basis for empowering human resources to improve quality, so that SMK Miftahul